Absolute Truth and Unbearable Psychic Pain : Psychoanalytic Perspectives on Concrete Experience - Frosch, Allan (CIPS series on the boundaries of psychoanalysis., 2012)
The title of this book refers to a particular construction of the world that brooks no uncertainty: 'things are the way I believe them to be'. There is no other way! This can be a real boost to one's confidence - even though this conviction is based solely on our own thoughts or immediate experience. When a group or organization share a one-dimensional view of the world the sense of conviction takes the form of a rigid ideology; and all other perspectives must be eliminated. The counterpart to concreteness, or what many refer to as desymbolized thinking/experience or thing - presentations, i.